IMPROVEMENT OF THE DIGITAL ECONOMY AND ITS SIGNIFICANCE IN HIGHER EDUCATION IN TASHKENT REGION (Uzbek Scholar Journal, 2023)
The relevance of the article is explained by the fact that information and communication technologies are currently an important basis for the development of the knowledge economy. The article discusses the main directions of organizational and economic development in the transition to a post-industrial society. The role of information technologies in the development of the digital economy is revealed. The article describes measures to increase the rate of economic growth and innovative development of society through the introduction of information technology.